1982
DOI: 10.1007/bf02011464
|View full text |Cite
|
Sign up to set email alerts
|

Yeast flora of grape berries during ripening

Abstract: The yeast flora associated with the surface of grapes during ripening was studied with regard to different sectors of the grape skin and the position in the bunch by means of traditional as well as more vigorous preisolation and precounting treatments. The yeast number per square centimeter of skin increases with ripening and is highest in the area immediately surrounding the stem. The cluster sector closer to the peduncle seems to constitute a favorable substrate for yeasts, hosting a resident flora about 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 6 publications
12
82
0
3
Order By: Relevance
“…The frequent occurrence of C. stellata in the samples is in agreement with earlier works that demonstrated that this yeast was normally associated with overripe and botrytized grape berries and musts obtained from botrytized grapes (e.g. Rosini et al, 1982;Jackson, 2000). Interestingly, many of our isolates identified by conventional taxonomic methods as C. stellata turned out to be much more osmotolerant and psychrotolerant than CBS 157 T , the type strain of C. stellata.…”
Section: Introductionsupporting
confidence: 91%
“…The frequent occurrence of C. stellata in the samples is in agreement with earlier works that demonstrated that this yeast was normally associated with overripe and botrytized grape berries and musts obtained from botrytized grapes (e.g. Rosini et al, 1982;Jackson, 2000). Interestingly, many of our isolates identified by conventional taxonomic methods as C. stellata turned out to be much more osmotolerant and psychrotolerant than CBS 157 T , the type strain of C. stellata.…”
Section: Introductionsupporting
confidence: 91%
“…Feeding by wasps and birds can break the skin of fruits (32,33), enabling insects for which intact fruits are too tough or provide insufficient gustatory stimuli to feed. Although skins of intact grapes harbor an indigenous yeast fauna (34), in our trials GJB were not attracted to artificially-wounded berries from unsprayed vines. JB facilitation of GJB therefore involves more than just JB feeding wounds allowing entry of indigenous surface yeasts.…”
Section: Role Of Yeasts In Gjb Attraction To Beetle-injured Grapesmentioning
confidence: 65%
“…None of the yeasts we found associated with beetles collected on grapevines in Kentucky were isolated from feces or guts of field-collected GJB in Arkansas, although 2 that we isolated from JB (D. hansenii and C. guilliermondii), and 2 others from GJB (R. glutinis and R. mucilaginosa) were found in GJB and on peaches in Oklahoma (34). Trichosporon cutaneum Ota, a yeast earlier workers (29,35) predicted to be central to production of compounds responsible for GJB aggregation, was absent in our samples.…”
Section: Role Of Yeasts In Gjb Attraction To Beetle-injured Grapesmentioning
confidence: 73%
“…C. stellata is found in the fermentation of sweet botrytized wines (in which grapes are affected by Botrytis cinerea) and overripe grapes (Rosini et al, 1982;Sipiczki, 2003) and is considered the main agent responsible for the wine aroma-compounds produced (Soden et al, 2000). Nevertheless, it has been demonstrated that in most cases St. bacillaris (C. zemplinina) and St. bombicola (Candida bombicola) have been incorrectly classified as C. stellata (Sipiczki, 2003(Sipiczki, , 2004Sipiczki et al, 2005;Csoma & Sipiczki, 2008).…”
Section: Discussionmentioning
confidence: 99%